2012
DOI: 10.7869/tg.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Lower chronic hepatitis B in South Asia despite all odds: Bucking the trend of other infectious diseases

Abstract: Hepatitis B virus (HBV) infection remains a significant global health problem. As per estimates of the World Health Organization (WHO), approximately 2 billion people have been infected worldwide, which represents one-third of the world population. Of these, more than 350 million (5-7% of the world's population) suffer from chronic HBV infection. 1,2 Approximately 15-40% of the infected patients will develop life-threatening liver diseases (cirrhosis, liver failure and hepatocellular carcinoma) resulting in 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…HBsAg prevalence in pregnant women is estimated to be 0•4% in the rural population and 3•5% in urban regions. 8 HCV prevalence varies considerably, from 0•8% among truck drivers to 24•8% among people who inject drugs. 7 12-18 million people (0•96-1•4% of the population) are thought to be infected with HCV in India, 9 and more than 37 million people (2•55% of the population) have chronic HBV infection 10 -with the highest prevalence in specifi c areas or among tribal populations.…”
Section: Epidemiological Overviewmentioning
confidence: 99%
“…HBsAg prevalence in pregnant women is estimated to be 0•4% in the rural population and 3•5% in urban regions. 8 HCV prevalence varies considerably, from 0•8% among truck drivers to 24•8% among people who inject drugs. 7 12-18 million people (0•96-1•4% of the population) are thought to be infected with HCV in India, 9 and more than 37 million people (2•55% of the population) have chronic HBV infection 10 -with the highest prevalence in specifi c areas or among tribal populations.…”
Section: Epidemiological Overviewmentioning
confidence: 99%
“…55 Despite the lower socio-economic status, illiteracy, low immunization rates, regional conflict and high-risk tribal populations, the prevalence of HBV is lower in India and the rest of South Asia as compared to South-East Asia. 56 Despite all the odds, this lower prevalence of HBV in South Asia may be due to the fact that unlike the vertical transmission of HBV in South-East Asia, the predominant mode of transmission is horizontally in South Asia. 57,58 Chronic HBV infection in India is acquired in childhood, presumably before 5 years of age, through horizontal transmission.…”
Section: Risk Factors and Transmission In High-risk Personsmentioning
confidence: 99%
“…9 The overall rate of HBsAg positivity has been reported to range between 2 and 4.7%. 10 The seroprevalence of HBsAg of 2.8% was noted in our tertiary care hospital population. A recent study conducted by Sood and Nalwankar 2 from Jaipur showed seroprevalence of HBsAg to be 0.87%.…”
Section: Discussionmentioning
confidence: 68%